Climate cooperation with technology investments and border carbon adjustment - Carsten Helm; Robert C. Schmidt (University of Oldenburg, Department of Economics, 2014)
A central question in climate policy is whether early investments in low-carbon technologies are a useful first step towards a more effective climate agreement in the future. We introduce a climate cooperation model with endogenous R&D investments where countries protect their international competitiveness via border carbon adjustments (BCA). BCA raises the scope for cooperation and leads to a non-trivial relation between countries' prior R&D investments and participation in the coalition. We find that early investments in R&D render free-riding more attractive. Therefore, with delayed cooperation on emission abatement and ex-ante R&D investments, the outcome is often characterized by high participation but inefficiently low technology investments and abatement.
Keywords: D62; F53; H23; Q55; 330; climate treaty; border carbon adjustment; border tax adjustment; coalitions; R&D